Роль корпоративної культури у підвищенні якості підготовки студентів-менеджерів вищого технічного навчального закладу - Шаполова, Вікторія Валеріївна (НТУ "ХПІ", 2011)
Еxamined the role of corporate culture to the university, to its image, to the formation of the future manager who is able to compete in the labor market. The essence of the concept “corporate culture” is clarified; the functions and components of corporate culture for student’s social and cultural environment and higher technical educational establishments are disclosed.
Keywords: корпоративна культура; підготовка студентів-менеджерів; формування корпоративних цінностей; культурно-естетичні потреби майбутнього фахівця